BETWEEN POWERS AND INVISIBILITIES:: LGBTI+ PEOPLE IN THE BRAZILIAN LEGISLATIVE POWER - Dias Oliveira, Victor Leonardo; de Andrade Gomes, Rayane Cristina (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
The LGBTI+ body is a political body and is crossed by several developments given the historical formation of the Modern State. This work investigates the movement of candidacies and elections of LGBTI+ people for the Brazilian Legislative Branch, after the 1988 Constitution until 2022, the last election when the research was carried out. A research of a basic nature was used, while it can also be applied, of a mixed type (exploratory-descriptive), of a quantitative-qualitative approach, of a deductive and bibliographic-documentary method, based on historical rescues made by some authors , such as Cruz (2015), Santos (2016), Pereira (2017), Pereira (2018), Pereira (2022), Quinalha (2023), based on data produced by organizations of the LGBTI+ movement, notably ABGLT, ANTRA, the National LGBTI Alliance, #MeRepresenta and #VoteLGBT, and other means (interviews, reports, social networks) to identify self-declaration of gender and sexual orientation, with a view to lack of official data produced by the Public Authorities. In summary, it was found that there is a significant increase in the number of candidacies and elections of LGBTI+ people for the Brazilian parliament, however, this does not necessarily contribute to a greater space for this population to speak, much less, reducing discrimination and social exclusion.